IMPLEMENTASI STRATEGI PEMERINTAH DALAM PENANGANAN PANDEMI COVID-19 DALAM WILAYAH JAWA-BALI - Ruth Elizabeth Marlamb Putri (Jurnal Hukum Adigama, 2021)
The Pandemic Coronavirus Disease (Covid-19) entered Indonesia on March 2, 2020 when the first positive case was confirmed against an Indonesian citizen. The impact arising from the Covid-19 pandemic on the life of the nation and state in Indonesia is very large, affecting various sectors, namely health, economy, law, religion, culture, and so on. This has prompted the Government of Indonesia to make various efforts to overcome this Pandemic, including the making of laws and regulations related to Covid-19, Large-Scale Social Restrictions (PSBB) carried out by the Central Government and Regional Governments in monitoring the spread of Covid-19 in Indonesia and policies issued by the government as a government approach to the community through the Provision of Social Assistance Funds and so on. All of this is done with the hope that the Covid-19 pandemic problem can be resolved soon. However, along with the implementation process, it is undeniable that a number of problems also arise. The changes that occur to the legal system in Indonesia force people to adapt to a new habit which is certainly difficult to do, especially for people whose economy can be categorized as poor.